Small-Scale Laboratory Activities Integrated With Central Lombok Culture In Chemistry Learning: An Empirical Study Of Chemistry Teachers' Perceptions - Junaidi, Eka; Savalas, Lalu Rudyat Telly; Muti’ah, Muti’ah; Sofia, Baiq Fara Dwirani; Hidayanti, Ermia (Chemistry Education Practice, 2023)
Chemistry learning is currently directed at using the surrounding culture and supporting the concept of green chemistry in its implementation. Cultures in Central Lombok, West Nusa Tenggara Province, have the potential to be integrated with the surrounding culture in the chemistry learning process. Small-scale laboratory work can be an option to support environmental conservation. Until now, the integration of the two has not been studied much in the chemistry learning process. This research aims to analyze chemistry teachers' perceptions of micro-scale labs combined with Central Lombok culture and identify variables that influence chemistry teachers' perceptions of micro-scale labs combined with Central Lombok culture. The research sample was taken randomly from 84 chemistry teachers who taught on Lombok Island. Sample demographics are based on education, teaching location, age, gender, and employment status. The study results showed significant differences between chemistry teachers' perceptions and differences in last education and teaching location. In contrast, differences in age, gender, and employment status did not significantly influence the aspects measured. Free response data shows that there needs to be a study and development of learning resources that guide teachers in implementing small-scale laboratories, using the surrounding culture, and integrating the two in chemistry learning.